ОЛИЙ ҲАРБИЙ ТАЪЛИМ МУАССАСАЛАРИ ҲАРБИЙ ПЕДАГОГ КАДРЛАРНИ ТАЙЁРЛАШ ТИЗИМИНИ ТАКОМИЛЛАШТИРИШДА ҲАЛҚАРО ТАЖРИБАНИНГ ТАҲЛИЛИ - Акбарходжаев, К.А. (SCIENCE and SOCIETY, 2024)
This article describes the important features of the military education system in developed foreign countries, the main requirements for teachers of higher military educational institutions, and the stages of training and professional development of professors.